Copyright Perspective in the Multiplicity of Batik Motifs as a Reflection of the National Character Identity - Megawati Atiyatunnajah; Nilnarohmah (LEGAL BRIEF, 2023)
In the face of globalization challenges, it is important to preserve cultural diversity and protect batik heritage as a symbol of national cultural identity. The copyright approach is used as a legal framework for the protection and utilization of batik works. To determine the most original identity with its uniqueness is actually impossible, as no nation in the world is completely different from others. However, the multiplicity of batik motifs can contribute to the characteristics of the Indonesian nation. Batik is a national creative work that must be preserved. The aim of this research is to analyze how the perspective of copyright can influence the understanding, recognition, and development of batik as a cultural heritage. The research method used is literature review by analyzing literature related to batik, copyright, and cultural identity. The results of this research indicate that the perspective of copyright provides important legal protection in securing the authenticity and commercialization of batik. However, copyright protection must also be balanced with efforts to maintain sustainability and social justice for traditional batik makers. This research concludes that through a proper understanding of copyright, steps can be taken to strengthen the national character identity reflected in the diversity of batik motifs. This research has significant implications for policymakers, cultural stakeholders, and society in preserving and promoting Indonesia's valuable cultural heritage. This article analyzes the relevant legal framework, including copyright laws and intellectual property protection in Indonesia. In facing the challenges of copyright infringement, this article also proposes measures to strengthen legal protection for batik motifs as part of the national character identity. It is expected that this article can provide a better understanding of the copyright perspective in the diversity of batik motifs and contribute to the development of more effective legal policies in safeguarding Indonesia's cultural heritage.